Prognostic relevance of CD163+ immune cells in patients with metastatic breast cancer - Lindberg, Ida; Saleh, Aya; Tutzauer, Julia ; 0000-0001-8267-8445; Gunnarsdottir, Frida Björk; Rydén, Lisa ; 0000-0001-7515-3130; Bergenfelz, Caroline ; 0000-0001-9337-7285; Larsson, Anna Maria (Cancer Immunology, Immunotherapy, 2025)
Metastatic breast cancer (MBC) is generally considered an incurable disease and even though new treatments are available, the median survival is approximately three years. The introduction of immune therapies for MBC highlights the importance of the immune system in cancer progression and treatment. CD163+ anti-inflammatory myeloid cells, including tumor associated macrophages (TAMs), are known to be of relevance in early breast cancer but their role in MBC is not yet established. Here we determine the levels of CD163+ immune cells in 139 patients with newly diagnosed MBC by using Immunohistochemistry (IHC) and gene expression analyses (GEX). We aim to determine changes and distribution of CD163+ immune cells during tumor progression from primary tumors (PT) to lymph node metastases (LNM) and distant metastases (DM). In addition, we evaluate associations between CD163+ immune cells, clinicopathological factors and disease outcome (progression-free and overall survival; PFS and OS, respectively). Despite similar distribution, high levels of CD163+ immune cells in the tumor nest of PT, but not in LNM or DM, associated with adverse prognostic features including higher grade and molecular subtype, as well as with shorter PFS and OS, however this observation was not significant after adjusted multivariate analyses. Finally, high levels of CD163+ immune cells in PT, as well as GEX in PT and synchronous LNM associated with shorter OS from the initial diagnosis. These results indicate that evaluating the levels of CD163+ immune cells may identify MBC patients with a worse prognosis. Unraveling the role of CD163+ immune cells in the complex immune responses in MBC is highly relevant for improving future immune therapies.
Publisher Copyright: © The Author(s) 2024.
Keywords: CD163; Metastatic breast cancer; Myeloid cells; Prognosis; Tumor-associated macrophages